2020
DOI: 10.3390/w12071923
|View full text |Cite
|
Sign up to set email alerts
|

Water Use Strategies of Dominant Species (Caragana korshinskii and Reaumuria soongorica) in Natural Shrubs Based on Stable Isotopes in the Loess Hill, China

Abstract: Water is a key and limiting factor for ecosystem processes (carbon dioxide fixation, vegetation growth, respiration, etc.) and functions (NPP, Net Primary Productivity) in arid and semi-arid areas. As the main regulator, knowledge of plant water use patterns is essential in understanding the SPAC (Soil-Plant-Atmosphere-Continuum) cycle. The tree-planting project in the southern and northern mountains of Lanzhou city aims to improve the ecological environment and promote urban construction. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Lanzhou is a typical river valley city; the Yellow River runs through the city from west to east, and the southwest region has a higher altitude than the northeast. The altitude of most of the urban areas are between 1500 and 2500 m a.s.l., with beaded valley landforms alternating between canyons and basins [31]. Lanzhou is located in the temperate semi-arid continental monsoon climate zone, with an annual average temperature of 10.3 • C and an annual average precipitation of 324.9 mm, delivered mainly from July to September [31,32].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Lanzhou is a typical river valley city; the Yellow River runs through the city from west to east, and the southwest region has a higher altitude than the northeast. The altitude of most of the urban areas are between 1500 and 2500 m a.s.l., with beaded valley landforms alternating between canyons and basins [31]. Lanzhou is located in the temperate semi-arid continental monsoon climate zone, with an annual average temperature of 10.3 • C and an annual average precipitation of 324.9 mm, delivered mainly from July to September [31,32].…”
Section: Study Areamentioning
confidence: 99%
“…The altitude of most of the urban areas are between 1500 and 2500 m a.s.l., with beaded valley landforms alternating between canyons and basins [31]. Lanzhou is located in the temperate semi-arid continental monsoon climate zone, with an annual average temperature of 10.3 • C and an annual average precipitation of 324.9 mm, delivered mainly from July to September [31,32]. The Lanzhou section of the Yellow River is 152 km long, 45 km of which flows through urban areas.…”
Section: Study Areamentioning
confidence: 99%
“…Due to the dry climate, strong evaporation and deeply buried groundwater (>120 m) in hillside habitat, thus it is difficult for vegetation to absorb and use the groundwater. Considering this, soil water at different depths is considered as a potential water source for hillside habitat [34]. The interaction between river water and groundwater in the floodplain habitat is relatively strong, leading to a similar isotopic value between river and groundwater, so they are regarded as the same water source in the floodplain habitat [29].…”
Section: Division Of Plant Water Sourcesmentioning
confidence: 99%
“…It was found that shallow soil water was the main source of water for T. ramosissima, and in low soil moisture months, T. ramosissima increased the use of deep soil water and river water [33]. Other studies on the water sources of plants in Lanzhou City have mainly focused on the foothills and hillside habitats [31,34]. Nevertheless, there were fewer comparative studies on different habitats.…”
Section: Introductionmentioning
confidence: 99%
“…[40]. Research on plant water uptake by using stable isotope technology and related mathematical models mainly focused on arid and semi-arid areas [14,[47][48][49][50]. However, only a few studies have been conducted on plant water use in subtropical humid areas.…”
Section: Introductionmentioning
confidence: 99%